Persepsi Petani terhadap Pelestarian Pertanian Sawah Sistem Subak di Perkotaan - KADEK BUDI PRADNYANA; WAYAN GINARSA; WAYAN SUDARTA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2012)
ABSTRACT Perception of Farmers Towards Conservation of Agricultural Field with Subak System in Urban Setting Subak is a Balinese cultural heritage in the form of an irrigation system that regulates the distribution of water management based on the mindset of harmony and togetherness, which is based on formal rules and religious values. The most obvious drawback of this traditional irrigation system is inability to block out the damaging artifact, which manifests itself in the form of land use so, the existence of this traditional irrigation system including the subak system in Bali to be difficult to implement. Site selection research done on purpose (purposive) with consideration of Subak Buaji having land uses competition. Subak Buaji is one of available subak in urban areas who had of farmers decrease in the last five years. Respondents in this research is 30 people were taken from 297 farmers with a purposive sampling method. The results shows that the perception farmers of the preservation of agricultural fields in the urban system in Subak Buaji, Village Kesiman, District of East Denpasar, Denpasar categorized either by the achievement score of 81.07% which means that urban farmers have a good perception of the existence of subak system of agricultural fields. Perception in this assessment is reviewed from three aspects including economic, social and cultural aspects and technical aspects. Based on the research of urban farmers are advised to keep making the agricultural sector as a livelihood without having to sell the farm. For agricultural extension agents as the sole government stooge and as agent of change, should be able to provide solutions to problems and participate saprodi anticipate land which is a big problem for the agricultural sector. Keyword: subak system, perception